An Overview of the Synthesis of Highly Versatile N-Hydroxysuccinimide Esters - Barré, Anaïs; Ţînţaş, Mihaela-Liliana; Levacher, Vincent; Papamicaël, Cyril; Gembus, Vincent (Synthesis, 2017)
N-Hydroxysuccinimide esters (NHS-esters) are important and widely used tools in various areas of chemistry including peptide synthesis, bioconjugate chemistry, functionalized materials and polymers. The usual strategy employed to prepare these active esters generally relies on the coupling reaction with a carboxylic acid and N-hydroxysuccinimide in the presence of a coupling agent. However, more recently, many other efficient strategies have emerged in the literature. This short review covers the literature devoted to the preparation of these valuable N-hydroxysuccinimide esters.1 Introduction2 N-Hydroxysuccinimide Coupling Reaction with Activated Carboxylic Acids3 Carboxylic Acid Coupling Reaction with Activated N-Hydroxysuccinimide4 Alcohol and Aldehyde Coupling Reaction with N-Hydroxysuccinimide under Oxidizing Conditions5 Carbonylative Cross-Coupling Reaction6 Conclusion
Keywords: N-hydroxysuccinimide esters; reactive ester; amine-reactive crosslinker; synthesis; activated carboxylic acid